2018
DOI: 10.1101/405506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ECM deposition is driven by caveolin1-dependent regulation of exosomal biogenesis and cargo sorting

Abstract: The composition and physical properties of the extracellular matrix (ECM) critically influence tumour cell behaviour, and ECM deposition and remodelling by stromal fibroblast populations is therefore pivotal for tumour progression. The molecular mechanisms by which stromal and tumour cell populations regulate ECM layering are poorly understood. Tumour-stroma interaction is critically dependent on cell-cell communication mediated by exosomes, small vesicles secreted by most cell types and generated within multi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…36 Moreover, Cav1/ caveolae have been also shown to regulate FN internalization and degradation and more recently with the secretion of FN via exosome-regulated process. 37 Additional studies will be required to define the specific mechanism by which EC Cav1/caveolae controls ECM changes in athero-prone areas during the progression of atherosclerosis but it is likely that a combination of the processes described above might contribute to the alteration in ECM composition observed in Cav1 deficient mice. Moreover, we also found that absence of Cav1 in ECs expose to disturbed flow impairs the activation of NFkB signaling pathway and attenuates the OSS-primed inflammatory response to pro-atherogenic cytokines including TNFα and IL1β.…”
Section: Discussionmentioning
confidence: 99%
“…36 Moreover, Cav1/ caveolae have been also shown to regulate FN internalization and degradation and more recently with the secretion of FN via exosome-regulated process. 37 Additional studies will be required to define the specific mechanism by which EC Cav1/caveolae controls ECM changes in athero-prone areas during the progression of atherosclerosis but it is likely that a combination of the processes described above might contribute to the alteration in ECM composition observed in Cav1 deficient mice. Moreover, we also found that absence of Cav1 in ECs expose to disturbed flow impairs the activation of NFkB signaling pathway and attenuates the OSS-primed inflammatory response to pro-atherogenic cytokines including TNFα and IL1β.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure and composition, including ECM-associated proteins such as growth factors, control most if not all aspects of tumor pathology (58)(59)(60). It is now evident that EVs have an essential role in the ECM biology: EVs can be functional components of the ECM (32,34) and CM-EVs control ECM deposition (61) and remodeling (62). Our work provides a first evidence that CAFs deposit EVs in the matrix and that MBVs play a key role as vehicles for intercellular protein transfer.…”
Section: Discussionmentioning
confidence: 69%